Epidemiology of Hypertensive State among Chinese Migrants: Effects of Unaffordable Medical Care - Ming Guan (International Journal of Hypertension)
Hypertension is a major risk factor for heart disease and stroke. Affordability of medical care affects hypertension prevention, treatment, and control, but limited information is available for Chinese migrants with hypertensive state. Using Longitudinal Survey on Rural Urban Migration in China 2009 data, 2468 Chinese migrants reported hypertensive status. On the basis of comparison between medical payment and job income, participants were categorized as unaffordable and affordable. Thus, unaffordable expenses and unaffordable services were defined based on a public available survey. The descriptive statistics showed that 24.96% were at risk of prehypertension and mild-moderate-severe hypertension among 2468 Chinese migrants from 15 cities. Small part of the sample was not affordable to pay medical expenses and services. There were significant differences of hypertensive states between gender, marital status, regular smoker, and economic unaffordability. Multiple logistic regressions indicated that economic unaffordability had associations with abnormal weight, poor health assessment, and unhealthy hypertensive status. The alarming results may necessitate targeted interventions, even among people with good health status.